Fluorescein-Guided Surgery for Pediatric Brainstem Gliomas: Preliminary Study and Technical Notes - Xue, Zhan; Kong, Lu; Pan, Chang-cun; Wu, Zhen; Zhang, Jun-ting; Zhang, Li-wei (Journal of Neurological Surgery Part B: Skull Base, 2018)
Introduction Brainstem gliomas (BsG) account for 10 to 15% of pediatric brain tumors. Surgery is the preferred treatment for focal and exophytic lesions. Sodium fluorescein has been proven safe and effective in resection of malignant brain tumors.Objective The objective was to o analyze the safety and effectiveness of this approach, to evaluate intraoperative fluorescein imaging, and to measure the safety of chosen dose for pediatric patients.Methods Twelve cases were enrolled between March 2014 and September 2016 in Beijing Tiantan Hospital. All of the patients received 2.5 mg/kg of sodium fluorescein before opening the dura; the intraoperative fluorescence enhancement was observed, and the degree of satisfaction and consistency with the neuronavigation were evaluated.Results With a mean age of 7.5 years, there were eight cases located within the pontine, three in the medullary oblongata, and one in the tectal plate. Histological results were astrocytoma, glioblastoma, oligodendroglioma, and pilocytic astrocytoma. Under the fluorescein module of the microscope, the tumors were recognizable enough to help surgeons to discriminate the lesion from non-fluorescent tissue, with a consistency of 83% with the neuronavigation. Total removal was accomplished in nine cases, while the mean percentage of resection of the other cases was 93.7%. The Karnofsky performance score (KPS) showed no significant differences between pre-operation and discharge, but there was a difference between pre-operation and 6-month follow-up.Conclusion The fluorescein-guided surgery is useful for demarcating the tumor margin and works well with other navigation and monitoring devices. A safe dose of sodium fluorescein (2.5 mg/kg) was proven effective for children.
Keywords: sodium fluorescein; pediatric brainstem gliomas; yellow 560 nm; surgery; safe dose